Measurement of τ polarisation in Z/γ∗→ττ decays in proton-proton collisions at √s=8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2018)
This paper presents a measurement of the polarisation of τ leptons produced in Z/γ ∗ → τ τ decays which is performed with a dataset of proton—proton collisions at √s = 8 TeV, corresponding to an integrated luminosity of 20.2 fb−1 recorded with the ATLAS detector at the LHC in 2012. The Z/γ ∗ → τ τ decays are reconstructed from a hadronically decaying τ lepton with a single charged particle in the final state, accompanied by a τ lepton that decays leptonically. The τ polarisation is inferred from the relative fraction of energy carried by charged and neutral hadrons in the hadronic τ decays. The polarisation is measured in a fiducial region that corresponds to the kinematic region accessible to this analysis. The τ polarisation extracted over the full phase space within the Z/γ ∗ mass range of 66 < mZ/γ ∗ < 116 GeV is found to be Pτ = −0.14±0.02(stat)±0.04(syst). It is in agreement with the Standard Model prediction of Pτ = −0.1517 ± 0.0019, which is obtained from the ALPGEN event generator interfaced with the PYTHIA 6 parton shower modelling and the TAUOLA τ decay library.